Cervical cancer screening before hysterectomy in pelvic organ prolapse patients: Is it essential? A case series - Aryasatiani, Ekarini; Surya, Raymond; Harjanti, Dyonesia Ary; Ilona, Florinda; Kartika, Chandra Dewi; Cantika, Catalya Christina; Tenka, Lisda (Universitas Airlangga, 2025)
HIGHLIGHTS More advanced cervical precancerous histopathological findings compared with cervical cytology are observed in POP patients undergoing vaginal hysterectomy. Routine use of preoperative biopsy or ultrasound in POP patients undergoing vaginal hysterectomy cannot be recommended. ABSTRACT Objective: Pelvic organ prolapse (POP) results from weakening of the pelvic floor musculature. The reported prevalence of unexpected premalignant and malignant pathologies following hysterectomy ranges from 0.2 to 0.8%. This study aims to present a case series of patients with POP who underwent vaginal hysterectomy (VH) after preoperative evaluation for abnormal cervical cytology, which subsequently demonstrated more advanced histopathological findings. Case Series: Case 1: A 55-year-old woman, P3A0, was diagnosed with third-degree uterine prolapse and cystocele. Pap smear revealed atypical glandular cells of undetermined significance (AGUS). Histopathological examination after VH demonstrated vaginitis and metaplastic chronic cervicitis with atypia progressing to mild dysplasia of endocervical epithelial cells/low-grade squamous intraepithelial lesion (LSIL). Case 2: A 62-year-old woman, P5A0, was diagnosed with third-degree uterine prolapse. Pap smear revealed atypical squamous cells of undetermined significance (ASCH). Histopathological evaluation after VH demonstrated high-grade squamous intraepithelial lesion (HSIL) up to carcinoma in situ with microinvasive glandular involvement and focal extension. Conclusion: Given that cervical cancer remains the second leading cause of mortality among women in Indonesia, preoperative screening for precancerous gynecological lesions and malignancy is strongly recommended.